Identification of RAD51AP1 as a key gene in hepatitis B virus-associated hepatocellular carcinoma - Meiling Wan; Yonghong Wang; Xiaoling Liu; Yaling Li; Cunliang Deng; Changfeng Sun (Heliyon)
Background: Hepatocellular carcinoma (HCC) is a significant global health concern, with chronic hepatitis B virus (HBV) infection being a major contributor. Understanding the mechanisms of HBV-associated HCC is crucial to improving the prognosis and developing effective treatments. Methods: HBV-associated HCC datasets (GSE19665, GSE121248, GSE55092, GSE94660, and TCGA-LIHC) acquired from public databases were mined to identify key driver genes by differentially expressed gene analysis, weighted gene co-expression network analysis (WGCNA), followed by protein-protein interaction network analysis, Lasso-Cox regression analysis, and randomforestSRC algorithm. Then, in vitro experiments including CCK-8 assay, wound healing, and Transwell assay were performed to explore the functions and mechanisms. Results: RAD51AP1 was identified as a specific key gene linked to the progression of HBV-associated HCC. High expression of RAD51AP1 was associated with worse overall survival (OS) in patients with HBV-associated HCC, but not in patients with non-HBV-associated HCC. Mechanistically, RAD51AP1 forms a potential ceRNA axis with LINC01419 and miR-8070, where LINC01419 acts as a molecular sponge for miR-8070 to upregulate RAD51AP1. HBV infection can enhance the LINC01419/miR-8070/RAD51AP1 axis, and LINC01419 overexpression conversely promotes HBV replication. The ceRNA axis and HBV synergistically promote the proliferation and metastasis of HBV-associated HCC cells. Furthermore, LINC01419 or RAD51AP1 knockdown, and miR-8070 overexpression in HepG2.2.15 cells significantly attenuated the Wnt/β-catenin signaling. Conclusions: The LINC01419/miR-8070/RAD51AP1 axis promotes the HBV-associated HCC progression through an HBV-boosted positive feedback loop and Wnt/β-catenin signaling. These findings provide novel insights into the underlying mechanisms and may offer potential diagnostic and therapeutic targets in HBV-associated HCC.